IMPLEMENTASI HARMONISASI SAINS DAN AGAMA DI UIN GUS DUR BERBASIS PRINSIP, PENDEKATAN, DAN LANGKAH STRATEGIS - Mutiara As'syifa, Rahma; Mutoharoh , Aenun; Prayogi, Arditya; Indah Lestari , Kartini (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
This study aims to explore the implementation of science and religion harmonization at the State Islamic University (UIN) KH. Abdurrahman Wahid, better known as UIN Gus Dur, with a focus on the principles, approaches, and strategic steps implemented to promote scientific integration. The harmonization of science and religion is an effort to bridge scientific rationality with Islamic spirituality, thereby overcoming the dualism between modern knowledge and religious teachings. Using a qualitative approach through a literature review and institutional policy analysis, this study reveals that the harmonization process at UIN Gus Dur is based on integrative-holistic principles and applies an integrated framework that connects faith and knowledge. Strategic efforts include curriculum improvement, faculty development, and the promotion of collaborative research. These initiatives reflect UIN Gus Dur's commitment to building a scientific paradigm rooted in Islamic values ​​while remaining adaptive to advances in modern science.